Association Between Parenting Styles, Children’s Nutritional Status, and Quality of Life among Children Ages 8-12 Years - Vivian Angelina Harsono; Edward Surjono; Ellen Wijaya; Andy Setiawan (Faculty of Medicine, Universitas Padjadjaran, 2022)
Nutritional status and parenting styles are two factors that are thought to affect children’s quality of life. This study aimed to assess the relationship between parenting styles, nutritional status, and quality of life of children aged 8-12 years. This cross-sectional observational analytic study used data collected from November 2020 to January 2021 using the Parenting Styles and Dimensions Questionnaire (PSDQ) and Pediatric Quality of Life Inventory (PedsQL) that were distributed in the form of e-questionnaire . The analysis tests used were the Spearman and logistic regression tests with a level of significance of 0.05. The results of the Spearman test showed that there was no correlation between parenting style and quality of life (p = 0.882) and between the nutritional status and quality of life (p = 0.568). The results of the logistic regression analysis showed that the variables of parenting (p = 0.437; 95% CI = 0.607–3.174; OR = 1.388) and nutritional status (p = 0.432; 95% CI = 0.504–1.341; OR = 0.822) were not associated with quality of life. Thus, there is no significant relationship between parenting patterns and children's nutritional status on the quality of life of children aged 8-12 years.